(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
This article analyzes the appearance in the minds of readers of the character of the protagonist of the cycle of novels by B. Akunin Erast Petrovich Fandorin, a young policeman endowed with great intellectual abilities, analytical composition of reason, fearlessness and bravery, and the ability to predict the following situations. For this, the author analyzes the first work of the cycle, the novel “Azazel”, written by B. Akunin in 1998. The fictional biography of the hero of this novel marked the beginning of the great mystique of the writer, which resulted in the quasi-biography in the subsequent works of the cycle.